Does pelvic injury trigger erectile dysfunction in men? - Ceylan, Hasan Hüseyin; Kuyucu, Ersin; Erdem, Remzi; Polat, Gökhan; Yılmaz, Ferit; Gümüş, Bilal; Erdil, Mehmet Emin (Elsevier, 2015)
Purpose: Pelvic ring fractures constitute 3%-8% of all fractures of the skeletal system and are generally related with high energy trauma. Sexual dysfunction following pelvic fracture has a high incidence, and affects the male patients both physically and psychologically. In this study, we aimed to investigate the impact and frequencies of comorbidities such as erectile dysfunction (ED) with adverse sociocultural and psychological consequences for the patient who had a pelvic ring fracture. Methods: This study included 26 men who corresponded to the inclusion criteria and agreed to participate our study. Results: According to fracture types, most of our cases were Tile type A1 and type A2. Severe and moderate ED were detected in 46.1% (12/26) of these patients via the International Index of Erectile Function-5 questionnaire. Conclusion: ED develops following pelvic fractures, especially in Tile type B and C pelvic fractures.
WOS: 000442089500008
PubMed ID: 26764545
Keywords: Erectile Dysfunction; Fractures; Pelvis; Bone